Menopause and Biopsychosocial Factors Associated with Quality of Life in Women in Surakarta, Central Java - Ermawati, Dwi Hesti; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Women spend a third of life during menopause. The number of women entering menopause worldwide is estimated at 25 million annually. Women of menopausal age have decreased estrogen hormone which can decrease the quality of life. This study aimed to analyze the biopsychosocial factors and menopause affecting the women's quality of life.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted in Surakarta, from January to February 2018. A sample of 200 women was selected by cluster sampling. The dependent variable was quality of life. The independent variables were self-efficacy, healthy behavior, menopause, and social support. The data were collected by questionnaire and analyzed by path analysis.Results: Womens quality of life increased with healthy behavior (b= 0.96; 95% CI= 0.35 to 1.56; p=0.002) and decreased by menopause (b= -0.96; 95% CI= -1.56 to -0.35; p= 0.002). Womens quality of life was indirectly affected by self-efficacy and social support.Conclusion: Womens quality of life is affected by menopause, healthy behavior, self-efficacy, and social support.Keywords: quality of life, women, biopsychosocial, menopauseCorrespondence:Dwi Hesti Ermawati, Masters Program in Public Health, UniversitasSebelasMaret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: dwihestirose@gmail.comJournal of Maternal and Child Health (2018), 3(2): 119-127https://doi.org/10.26911/thejmch.2018.03.02.04